2015
DOI: 10.1002/mrd.22588
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP‐ribosyl)ation is involved in pro‐survival autophagy in porcine blastocysts

Abstract: Poly(ADP-ribosyl)ation (PARylation) prevents apoptosis through its involvement in pro-survival autophagy in cultured cells; whether or not the same is true for pre-implantation embryos has not yet been documented. In this study, we investigated the participation of PARylation and autophagy in in vitro porcine pre-implantation embryo development. The transcript levels of autophagy-related genes and poly(ADP-ribose) polymerase 1 (PARP1), an enzyme required for PARylation, were transiently up-regulated by fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Autophagy is a self-digestion process in cells, which plays an essential role in cell development and the cellular response to stress [46]. However, excessive autophagy triggers apoptosis-mediated cell death (also a known type of programmed cell death) [47]. Our results showed that the expression of autophagic marker LC3B-II was significantly increased and that of SQSTM1 was significantly reduced in FGSCs after treatment with C28 for 3h, which indicated that C28 induced FGSC autophagy.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Autophagy is a self-digestion process in cells, which plays an essential role in cell development and the cellular response to stress [46]. However, excessive autophagy triggers apoptosis-mediated cell death (also a known type of programmed cell death) [47]. Our results showed that the expression of autophagic marker LC3B-II was significantly increased and that of SQSTM1 was significantly reduced in FGSCs after treatment with C28 for 3h, which indicated that C28 induced FGSC autophagy.…”
Section: Discussionmentioning
confidence: 52%
“…Data are expressed as the mean ± SEM. Proposed model of the regulatory mechanism of C28-induced autophagy C28 induces autophagy in FGSCs by regulating H3k27ac [45][46][47], and enhances the expression of genes related to ER stress [49][50][51].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The physiology levels of autophagy are indispensable for blastocyst development in mice [30] and pigs [11]. On the contrary, excessive levels of autophagy are detrimental to blastocyst development [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ATG5-deleted mouse embryos arrested at the 4-cell stage [10]. Reduced levels of autophagy prevented porcine blastocyst formation [11,12]. It was worth noting that autophagy activity was preferentially restricted to TE cells relative to ICM cells in mouse blastocysts [13].…”
Section: Introductionmentioning
confidence: 99%
“…We detected the levels of different molecules downstream of EGFR and found that the expression of mTOR/p-Akt was significantly different in cancerous and paracancerous tissues, but the expression of PI3K was not different. Poly(ADP)-ribose polymerase-1 (PARP1) repairs single-strand breaks in DNA and is important in autophagy regulation 21 . Reactive oxygen species (ROS) induce PARP1 activity and autophagy, and PARP1 knockout cells display low levels of autophagy, suggesting a prosurvival role for autophagy and PARP1 activity 22 .…”
mentioning
confidence: 99%